Association of Indian bread wheat genotypes under different moisture regimes - Kumar, Vishnu; Tyagi, B. S.; Verma, Ajay; Sharma, Indu (The Indian Journal of Genetics and Plant Breeding, 2017)
Forty elite bread wheat genotypes were assessed under different moisture regimes to ascertain the extent of genetic diversity and were grouped in to eight clusters. In irrigated conditions, the inter cluster distances ranged from 1.66 (cluster IV to VIII) to 9.47 (cluster II to VII), whereas the range of inter cluster distances under water stress conditions obtained was from 1.98 to 9.10. On pooled basis, the clusters II, III and IV had the most divergent genotypes with high inter cluster distances. The genotype GW 273 performed well in severe water stress, while WR 544 and Raj 4037 were found promising under water stress at grain filling stage.